“CENAS EMBAÇADAS”: A RELAÇÃO ENTRE AS ESPACIALIDADES VIVENCIADAS POR JOVENS DO SEXO MASCULINO E A MORTE POR HOMICÍDIO NA CIDADE DE PONTA GROSSA – PR - Gomes, Fernando Bertani (2013)
This work aims to understand the relation between spatialities lived by masculine youths and death by homicide in the city of Ponta Grossa, Paraná. The violent deaths in the country have been concentrated in the age group of masculine youths. Considering this, were analyzed 79 police inquiries of homicides occurred between 2010 and 2011 of 13º Police Subdivision of Ponta Grossa and the Criminal Jurisdictions from the same city. The most victimized profile found in the documental analysis were of masculine people aged between 15 and 25 years, resident of poor peripheral areas of the city, with low schooling and involved with drugs. Thus, the research makes a methodological displacement of the dead bodies to forms of life vulnerable to die victim of homicide, taking as empiric referential youths in treatment of drugs in Therapeutic Community Marcos Fernandes Pinheiro, where were made 6 semi-structured interviews, by which was possible categorized the lived spatialities by masculine youths in which the violence and death are present as an inter-relational element. The spatialities as the street, village and traffic were analyzed through the solid agencements emphasizing the relations that give continuity to performances of violent masculinity and death, in its daily multiple faces. The spatial practices of masculine youths are plotted by elements that position them as vulnerable to die murdered, like performances of local masculinities intersecting to the territoriality of traffic of drugs.